(untitled) (Revista Cientifica Ingenio Magno, 2023)
: In the present work, a bibliographic review of works related to the avocado oil extraction process was carried out, such as the identification of the stages of the extraction process of this avocado by-product, additionally, the production, marketing and demand variables were identified. of avocado oil in Colombia, the avocado oil extraction process was evaluated by the hydrocavitation method, identifying the raw material preparation process, the avocado oil extraction process by hydrocavitation, summarizing it in a process flow diagram of avocado oil extraction by hydrocavitation, to start this study, management tools such as the 4 P’S, SWOT analysis, Porter forces, among others, were taken into account.